MODELING, SIMULATION AND PERFORMANCE EVALUATION OF PARABOLIC TROUGH SOLAR COLLECTOR POWER GENERATION SYSTEM - Mesfin, Mekuannint; Assefa, Abebayehu (Zede Journal of Ethiopian Engineers and Architects, 2023)
Model of a parabolic trough power plant, taking into consideration the different losses associated with collection of the solar irradiance and thermal losses is presented. MATLAB software is employed to model the power plant at reference state points. The code is then used to find the different reference values which are used as inputs for the TRNSYS programme implemented in the modeling and simulation of the power plant. TRNSYS software is used to simulate the performance of the model at off design weather conditions as well. Keywords: Parabolic Trough Collector (PTC); Heat Transfer Fluid (HTF); TRNSYS power plant model; STEC library; Solar Advisor Model (SAM); TRNSYS solar field model; Solar Electric Generation System (SEGS).